Effects of Transformational Leadership, Organisational Learning and Technological Innovation on Strategic Management Accounting in Thailand’s Financial Institutions - Phornlaphatrachakorn, Kornchai (Asian Journal of Business and Accounting, 2019)
Manuscript type: Research paper. Research aims: This study aims to investigate the effects of transformational leadership, organisational learning and technological innovation on strategic management accounting in Thailand’s financial institutions. Design/Methodology/Approach: Data were collected from 141 financial institutions in Thailand through a questionnaire survey. Hierarchical multiple regression analysis is conducted to examine the relationships. Research findings: The findings indicate that transformational leadership, organisational learning and technological innovation positively influence strategic management accounting. The results also indicate a positive relationship between strategic management accounting and firm performance. Theoretical contributions/Originality: This study expands on existing literature by investigating the role of transformational leadership, organisational learning and technological innovations as antecedents to the implementation of strategic management accounting. It thus extends on the applicability of strategic management accounting in helping financial institutions in Thailand to gain superior performance. Practitioner/Policy contributions: The results of this study suggest that executives of financial firms need to pay attention towards building and developing transformational leadership, organisational learning and technological innovation for strategic management accounting implementation. This can be achieved by leveraging on the firm’s competencies, capabilities, resources and assets. In other words, strategic management accounting can serve as a tool for organisations to gain a competitive edge in today’s dynamic business environment, thereby fulfilling firm performance. Research limitations/Implications: To increase the generalisability of this study, future research needs to collect data from a different set of population or country. This will help to expand on the database of the financial businesses throughout the world. Keywords: Transformational Leadership, Organisational Learning, Technological Innovation, Strategic Management Accounting, Firm Performance JEL Classification: M41